Comparison of the effects of three kinds of glucose‐lowering drugs on non‐alcoholic fatty liver disease in patients with type 2 diabetes: A randomized, open‐label, three‐arm, active control study - Kinoshita, Tomoe; Shimoda, Masashi; Nakashima, Koji; Fushimi, Yoshiro; Hirata, Yurie; Tanabe, Akihito; Tatsumi, Fuminori; Hirukawa, Hidenori; Sanada, Junpei; Kohara, Kenji; Irie, Shintaro; Kimura, Tomohiko; et al. (Journal of diabetes investigation, 2020)
Aims/Introduction Non‐alcoholic fatty liver disease (NAFLD) is often observed in individuals with type 2 diabetes mellitus, and it is known that the presence of type 2 diabetes mellitus leads to the aggravation of NAFLD. The aim of this study was to compare the possible effects of three kinds of oral hypoglycemic agents on NAFLD in individuals with type 2 diabetes mellitus. Materials and Methods We carried out a prospective clinical trial (a randomized and open‐label study) in patients with type 2 diabetes mellitus and NAFLD. A total of 98 patients were randomly allocated either to the dapagliflozin (n = 32), pioglitazone (n = 33) or glimepiride (n = 33) group, and the patients took these drugs for 28 weeks. The primary end‐point was the change of the liver‐to‐spleen ratio on abdominal computed tomography. Results There was no difference in baseline clinical characteristics among the three groups. Dapagliflozin, pioglitazone and glimepiride ameliorated hyperglycemia similarly. Bodyweight and visceral fat area were significantly decreased only in the dapagliflozin group. Serum adiponectin levels were markedly increased in the pioglitazone group compared with the other two groups. Dapagliflozin and pioglitazone, but not glimepiride, significantly increased the liver‐to‐spleen ratio, and the effects of dapagliflozin and pioglitazone on the liver‐to‐spleen ratio were comparable. Conclusions The present study showed that the decrease of visceral fat area and the increase of adiponectin level contributed to the improvement of NAFLD in patients with type 2 diabetes mellitus. Furthermore, dapagliflozin and pioglitazone exerted equivalent beneficial effects on NAFLD in patients with type 2 diabetes mellitus, although it seemed that these two drugs had different mechanisms of action. Dapagliflozin and pioglitazone exerted equivalent beneficial effects on non‐alcoholic fatty liver disease in subjects with type 2 diabetes mellitus, although it seemed that these two drugs had different mechanisms of action. Dapagliflozin reduced hepatic fat storage mainly through a decrease of fat quantity, but pioglitazone improved hepatic steatosis through upgrading fat quality. Lowered plasma glucose by glimepiride might inhibit worsening of hepatic steatosis.